PENGARUH MEKANISME INTERNAL CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DAMPAKNYA TERHADAP KINERJA KEUANGAN - Dewi, Cyntia Septian; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out the influence of corporate governance to the earning management andits impact to the financial performance. The sample of the research is all manufacturing companies which arelisted in Indonesia Stock Exchange in 2010-2013 periods. This research has been carried out the samplecollection technique by using purposive sampling and 40 companies have been obtained as samples. Thisresearch has been done by using multiple linear regressions and simple linear regressions analysis and the SPSSapplication instrument (Statistical Product and Service Solutions). The results of the research show that i.e: (1)simultaneously corporate governance has positive influence to the earning management. (2) managerialinstitution does not have any influence to the earning management, (3) institutional ownership has negativeinfluence to the earning management, (4) the proportion of board of independent commissioner have negativeinfluence to the earning management, (5) board of commissioner size has negative influence to the earningmanagement, (6) audit committee has negative influence to the earning management, (7) firm size has positiveinfluence to the earning management, (8) leverage does not have any influence to the earning management, (9)earning management does not have any influence to the financial performance.Keywords: Corporate governance, earningmanagement, financial performance.